ENHANCING STUDENTS` SKILL IN WRITING RECOUNT TEXT OF JUNIOR HIGH SCHOOL THROUGH PHOTOGRAPHY TECHNIQUE - Muhammad Saiful Amin; Muh Shofiyuddin (Wiralodra English Journal, 2026)
Writing is challenging for junior high school students. Many students struggle to express their thoughts in recount texts due to a lack of ideas, limited vocabulary, and poor understanding of organizational features of a text; this research seeks to evaluate the efficacy of photography techniques in improving students` ability to write recount texts. This quantitative research used a quasi-experimental design, involving 40 eighth-grade learners in a lower secondary school in Batealit separated into two cohorts, with the trial group received photography techniques, while the control class did not. Data collection was conducted through a written test, and SPSS 30.0 was used for analysis, which included normality, homogeneity using an independent-sample t-assessment; the results revealed a notable gap separating both groups, where the intervention class achieving a higher post-test mean score (M = 79.60, SD = 9.703) than the control class (M = 46.80, SD = 17.173), with p < 0.001. These findings confirm indicating that the baseline assumption was disproven while the competing assumption was validated. The study concludes that photography can be an effective technique to stimulate creativity, generate ideas, and enhance the structure of recount text, providing better engagement and outcomes compared to traditional methods.